Dental Students' Perceptions of Dentist-Patient Interactions: An Exploration of Empathy in Dental Students - Tobias Rodriguez; Lynn Beck; Karl Woodmansey; Eileen Hoskin (Kerman University of Medical Sciences, 2018)
Background and Objectives Healthcare providers must endeavor to treat patients with empathy if they expect to practice successfully. Empathy is especially relevant to dentists who provide treatment that is usually associated with pain and invasion of personal space boundaries. A 2011 study by Konrath and O'Brien showed that undergraduate college students have less empathy than the past generations. Anecdotal reports and the author's personal experiences also suggest a reduction in empathy among current dental students. This study was designed to assess empathy in a dental student cohort at a dental school in the United States. Methods This study examined empathy levels in third- and fourth-year dental students at a dental school in the United States using existing validated medical education psychometric assessments modified for dental education. Specifically, the Jefferson scale of physician empathy-health professional (JSPE-HP) and patient-practitioner orientation scale (PPOS) questionnaires were modified for use in the dental education domain by substituting the word "dentist" for "physician" and replacing "medical procedures" with "dental procedures." E-mails were sent to all 240 third- and fourth-year dental students at the Rutgers school of dental medicine (RSDM) inviting them to participate in a brief online survey about their perceptions of dentist-patient interactions. Results Of the 240 invited students, 84 participated in the survey (27%). All questions were answered with a high empathy rating except for two questions - "It is difficult for me to view things from my patient's perspective" and "I can treat and relate best to patients who look like me and have similar beliefs." The calculated Cronbach's coefficient alpha was 0.71 indicating acceptable internal consistency reliability. Conclusions This study did not confirm the hypothesis that students lacked empathy. Only two statements were answered in ways that suggested a decrease in empathic cognition. The responses to the open-ended questions provided an insight into the students' self-interested thought processes.